Aureobasidium pullulans: a microbiome-based perspective from global biomes to edible plant tissues - Bziuk, Nina; Wassermann, Birgit; Bickel, Samuel; Omidvar, Reza; Manica, Andrea; Berg, Gabriele (Frontiers in Plant Science, 2025)
Aureobasidium pullulans is a globally distributed fungus commonly found in plant-associated and anthropogenic environments. Known for its antagonistic activity against plant pathogens, it is widely used as a biocontrol agent in sustainable agriculture. Despite its prevalence in edible plant tissues and frequent environmental exposure, its broader role within microbiomes and potential relevance for human health remain underexplored. In this perspective article, we highlight the global distribution of A. pullulans based on publicly available sequencing data and examine its ecological function from a microbiome-based viewpoint. Our synthesis supports the view of A. pullulans as a safe, plant-beneficial symbiont with high value for sustainable crop protection and potential relevance for the One Health framework. Future microbiome research should further explore its functional roles within plant and human-associated microbiomes to better harness its benefits while ensuring biosafety across ecosystems.